Ketamine Versus Etomidate and Peri‐intubation Hypotension: A National Emergency Airway Registry Study. (18th July 2020) - April, Michael D.; Arana, Allyson; Schauer, Steven G.; Davis, William T.; Oliver, Joshua J.; Fantegrossi, Andrea; Summers, Shane M.; Maddry, Joseph K.; Walls, Ron M.; Brown, Calvin A.; ,
Abstract: Background: The hemodynamic impact of induction agents is a critically important consideration in emergency intubations. We assessed the relationship between peri‐intubation hypotension and the use of ketamine versus etomidate as an induction agent for emergency department (ED) intubation. Methods: We analyzed ED intubation data for patients aged >14 years from the National Emergency Airway Registry performed in 25 EDs during 2016 through 2018. We excluded patients with preintubation hypotension (systolic blood pressure <100 mm Hg) or cardiac arrest prior to intubation. The primary outcome was peri‐intubation hypotension. Secondary outcomes included interventions for hypotension (e.g., intravenous fluids or vasopressors). We report adjusted odds ratios (aOR) from multivariable logistic regression models controlling for patient demographics, difficult airway characteristics, and intubation modality. Results: There were 738 encounters with ketamine and 6, 068 with etomidate. Patients receiving ketamine were more likely to have difficult airway characteristics (effect size difference = 8.8%, 95% confidence interval [CI] = 5.3% to 12.4%) and to undergo intubation with video laryngoscopy (8.1%, 95% CI = 4.4% to 12.0%). Peri‐intubation hypotension incidence was 18.3% among patients receiving ketamine and 12.4% among patients receiving etomidate (effect size difference = 5.9%, 95% CI = 2.9% to 8.8%). Patients receiving ketamine were more likely to receive treatment for peri‐intubation hypotension (effect size difference = 6.5%, 95% CI = 3.9% to 9.3%). In logistic regression analyses, patients receiving ketamine remained at higher risk for peri‐intubation hypotension (aOR = 1.4, 95% CI = 1.2 to 1.7) and treatment for hypotension (aOR = 1.8, 95% CI = 1.4 to 2.0). There was no difference in the aOR of hypotension between patients receiving ketamine at doses ≤1.0 mg/kg versus >1.0 mg/kg or patients receiving etomidate at doses ≤0.3 mg/kg versus >0.3 mg/kg. Conclusions: Pending additional data, our results suggest that clinicians should not necessarily prioritize ketamine over etomidate based on concern for hemodynamic compromise among ED patients undergoing intubation.